2016
DOI: 10.1111/gcb.13484
|View full text |Cite
|
Sign up to set email alerts
|

Organism activity levels predict marine invertebrate survival during ancient global change extinctions

Abstract: Multistressor global change, the combined influence of ocean warming, acidification, and deoxygenation, poses a serious threat to marine organisms. Experimental studies imply that organisms with higher levels of activity should be more resilient, but testing this prediction and understanding organism vulnerability at a global scale, over evolutionary timescales, and in natural ecosystems remain challenging. The fossil record, which contains multiple extinctions triggered by multistressor global change, is idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 56 publications
(99 reference statements)
6
24
0
Order By: Relevance
“…) may have led to the preferential survival, and dominance of infaunal organisms following the extinction horizon in this location. Clapham () found that more motile organisms preferentially survived Mesozoic extinctions, suggesting that greater activity and therefore potentially higher respiratory physiology, controlled survival during extinction periods (Clapham ). Our data show little change in the taxonomic richness of facultatively motile taxa; however, abundance trends do show an increase in motility during the early Danian.…”
Section: Discussionmentioning
confidence: 99%
“…) may have led to the preferential survival, and dominance of infaunal organisms following the extinction horizon in this location. Clapham () found that more motile organisms preferentially survived Mesozoic extinctions, suggesting that greater activity and therefore potentially higher respiratory physiology, controlled survival during extinction periods (Clapham ). Our data show little change in the taxonomic richness of facultatively motile taxa; however, abundance trends do show an increase in motility during the early Danian.…”
Section: Discussionmentioning
confidence: 99%
“…These functional groups, although not particularly diverse, all display feeding strategies that are expected to fare well in a stressed, post‐extinction world (i.e. deposit‐feeding, mining and chemosymbiosis) (Foster & Twitchett ; Clapham ). Some functional groups, such as pelagic, fast‐moving carnivores, suffered a significant reduction in relative richness at the LTE, but then quickly recovered to pre‐extinction levels by the late Hettangian, reinforcing the idea that both vertebrates (Thorne et al .…”
Section: Discussionmentioning
confidence: 99%
“…Apart from selection against specific regions, ecosystems or habitats (Foster & Twitchett, ), other studies have suggested that traits such as skeletal composition, motility and feeding are also critical in explaining patterns of selectivity. Past extinction events associated with elevated CO 2 have been shown to be selective against epifaunal, sessile, suspension feeders (Bush & Bambach ; Foster & Twitchett ; Clapham ), and selective against heavily calcified organisms (Hautmann ; Knoll et al . ; Hautmann et al .…”
mentioning
confidence: 99%
“…On the other hand, deep-time fossil data cannot inform about the effects of direct human impacts. A rich literature exists on how lifestyles, habitats and organismic traits affected extinction risk under past climate change [45][46][47][48][49][50][51][52]. A pressing question is, of course, how well these ancient vulnerabilities reflect modern vulnerabilities, that is, to what extent are they conserved over time.…”
Section: Addressing Specific Questionsmentioning
confidence: 99%